2007
DOI: 10.2172/935427
|View full text |Cite
|
Sign up to set email alerts
|

Directing Matter and Energy: Five Challenges for Science and the Imagination

Abstract: Fabrication of new crystalline materials with atomic-level control. To understand charge ordering and screening in mixed valence oxides, this oxide superlattice has been designed, synthesized, and then spectroscopically characterized at the atomic scale using scanning transmission electron microscopy. In the false color elastic images, white stripes are layers of LaTiO3; purple stripes are SrTiO 3. Small images show individual atomic layers-in the topmost principal-component-filtered image, pink is lanthanum; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…In particular, extensive research has been focused on the ion irradiation of these metals [1,2] to elucidate the response of these materials to extreme-conditions, since the performance of materials in extreme environments poses several important fundamental questions about the behavior of condensed matter under far-from-equilibrium conditions which create challenges in materials design and synthesis [3]. During these researches, the conditions found in nuclear fusion reactors have boosted the current research, viz.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, extensive research has been focused on the ion irradiation of these metals [1,2] to elucidate the response of these materials to extreme-conditions, since the performance of materials in extreme environments poses several important fundamental questions about the behavior of condensed matter under far-from-equilibrium conditions which create challenges in materials design and synthesis [3]. During these researches, the conditions found in nuclear fusion reactors have boosted the current research, viz.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, atomic resolution imaging of molecules, small atom clusters or surface structures remains a Grand Challenge in basic sciences 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The material in bulk (50 nm particles), however, remains black and conducting. We have found that the surface W 6+ can be removed by washing with NaOH (aq), creating core-shell particles of Ti 1-x W x O 2 with a topmost layer or two of TiO 2 . This surface appears to be sufficiently conducting due to electron tunneling from W 4+ below the surface.…”
Section: Oxides As Supports and Catalystsmentioning
confidence: 99%
“…With DEMS, we have tracked the formation of CO 2 via CO 2 ++ , at m/z = 22 ( Figure 9). The mass spectrometric cyclic voltammogram (MSCV) for CO 2 showed a 2 to 3 fold greater current in the positive going sweep relative to the negative going sweep. The additional current is likely due to oxidative stripping of adsorbates formed at low potentials.…”
Section: Cfci Final Reportmentioning
confidence: 99%
See 1 more Smart Citation